Preliminary Review of Desktop-to-Web System Transformation of Data Input Process in Accounting Information System - Diana; Pinandito, Aryo; Pradana, Fajar (Journal of Information Technology and Computer Science, 2024)
The accounting information system is an important key to financial management, the information influences the company’s decisionmaking in determining its future strategy. However, before the development of web technology, current systems were usually implemented on desktop platforms. Over time, many obstacles were found during its implementation, which had an impact on time efficiency on staff performance. Therefore, in this study, a preliminary review assessment is made to find out whether the current desktop information system is still good for use or a web-based system is able to provide more performance, especially in terms of time efficiency. According to the results of this study, web information systems have better performance than desktops. With the transformation of the platform in the system, there was an increase in the use of time in carrying out input process activities of 35%.